2022
DOI: 10.1002/lno.12041
|View full text |Cite
|
Sign up to set email alerts
|

Brownification reduces oxygen gross primary production and community respiration and changes the phytoplankton community composition: An in situ mesocosm experiment with high‐frequency sensor measurements in a North Atlantic bay

Abstract: In recent decades, the increase in terrestrial inputs to freshwater and coastal ecosystems, especially occurring at northern latitudes, has led to a process of water color darkening known as "brownification." To assess how brownification affects plankton community composition and functioning in northern coastal areas, an in situ mesocosm experiment using a highly colored humic substance to simulate a brownification event was performed in a North Atlantic bay (Hopavågen, Norway) in August 2019. Manual sampling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 57 publications
(90 reference statements)
2
19
0
Order By: Relevance
“…The daily light integral, the quantity of photosynthetically active photons received on a 1 m 2 surface over a 1 d period 52 , was estimated using high-frequency PAR measurements at 1 m depth, with Eq. ( 1 ): …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The daily light integral, the quantity of photosynthetically active photons received on a 1 m 2 surface over a 1 d period 52 , was estimated using high-frequency PAR measurements at 1 m depth, with Eq. ( 1 ): …”
Section: Methodsmentioning
confidence: 99%
“…Then, hourly l rates were multiplied by 24 to obtain daily rates (d −1 ). Here, we assumed that losses occurred during the entire 24-h period, and hourly µ rates were multiplied by the duration of the increasing period, in hours, as growth only occurred during the increasing period 52 54 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the Chl a concentration and abundance might still not fully reflect phytoplankton biomass. Combining multiple methods: pigment analyses for the community composition (Soulié et al 2022) and image analyses for the community size structure (Dunker et al 2018) could be alternative approaches in future studies to provide faster and more reliable estimation of phytoplankton biomass and composition, as manual counting requires expertise and time.…”
Section: Discussionmentioning
confidence: 99%
“…Previous results have reported that increasing DOM concentrations impaired the photosynthesis of monospecific cultures of cyanobacterial and natural phytoplankton when combined with vertical mixing‐mediated light fluctuations (Helbling et al ., 2015). High terrestrial inputs promote changes toward communities dominated by microphytoplankton (Villafañe et al ., 2018); reductions in primary and bacterial production (Paczkowska et al ., 2020); respiration and Chl a (Soulié et al ., 2022); species richness and photosynthetic efficiency (Rasconi et al ., 2015), as well as in the trophic transfer efficiency toward consumers (Hébert et al ., 2022). By contrast, recent results obtained by Spilling et al .…”
Section: Introductionmentioning
confidence: 99%